La práctica de prueba en materia civil y mercantil en la Unión Europea en el marco del Reglamento 1206/2001 y su articulación con el Derecho español - Ybarra Bores, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2012)
Cross-border disputes are increasing every day and so the need for taking of evidence abroad is more frequent nowadays. The traditional Conventions of the Hague Conference of 1 March 1954, and the subsequent of 18 March 1970, showed us out of phase and not very effectives. The Regulation 1206/2001 brought about a great advance in this matter in the European Union framework, because its provisions rule a flexible process for taking evidence in other Member States. However, some important issues appear in Spanish Law when applying the said Regulation.
Keywords: Regulation 1206/2001; taking of evidence; requesting courts; requested courts; central bodies; request to take evidence